Amniotic Fluid: A Perspective on Promising Advances in the Prevention and Treatment of Necrotizing Enterocolitis - de Kroon, Rimke Romee; de Baat, Tessa; Senger, Stefania; van Weissenbruch, Mirjam Maria (Frontiers in Pediatrics, 2022)
Necrotizing enterocolitis (NEC) is a common and potentially fatal disease that typically affects preterm (PIs) and very low birth weight infants (VLBWIs). Although NEC has been extensively studied, the current therapeutic approaches are unsatisfactory. Due to the similarities in the composition between amniotic fluid (AF) and human breast milk (BM), which plays a protective role in the development of NEC in PIs and VLBWIs, it has been postulated that AF has similar effects on the outcome of NEC and potential therapeutic implications. AF has been long used for its diagnostic purposes and is often discarded after birth as ‘biological waste’. However, researchers have started to elucidate its therapeutic potential. Experimental studies in animal models have shown that diseases of various organ systems can possibly benefit from AF-based therapy. Hence, we have identified three approaches which show promising results for future clinical application in the prevention and/or treatment of NEC: (1) administration of processed AF (PAF) isolated from donor mothers, (2) administration of AF stem cells (AFSCs) and (3) administration of simulated AF (SAF) formulated to mimic the composition of physiological AF. We have highlighted the most important aspects that should be taken into account to guide further research on the clinical application of AF-based therapy. We hope that this review can provide a framework to identify the challenges of AF-based therapy and help to design future studies to better evaluate AF-based approaches for the treatment and/or prevention of NEC in PIs and VLBWIs.